Aerobic Exercise Training Adaptations Are Increased by Postexercise Carbohydrate-Protein Supplementation - Lisa Ferguson-Stegall; Erin McCleave; Zhenping Ding; Phillip G. Doerner III; Yang Liu; Bei Wang; Marin Healy; Maximilian Kleinert; Benjamin Dessard; David G. Lassiter; Lynne Kammer; John L. Ivy (Journal of Nutrition and Metabolism)
Carbohydrate-protein supplementation has been found to increase the rate of training adaptation when provided postresistance exercise. The present study compared the effects of a carbohydrate and protein supplement in the form of chocolate milk (CM), isocaloric carbohydrate (CHO), and placebo on training adaptations occurring over 4.5 weeks of aerobic exercise training. Thirty-two untrained subjects cycled 60 min/d, 5 d/wk for 4.5 wks at 75–80% of maximal oxygen consumption (VO2 max). Supplements were ingested immediately and 1 h after each exercise session. VO2 max and body composition were assessed before the start and end of training. VO2 max improvements were significantly greater in CM than CHO and placebo. Greater improvements in body composition, represented by a calculated lean and fat mass differential for whole body and trunk, were found in the CM group compared to CHO. We conclude supplementing with CM postexercise improves aerobic power and body composition more effectively than CHO alone.